INDONESIAN MUFASSIR PERSPECTIVE ON GENDER EQUALITY: STUDY ON TAFSIR AL-MISBAH, TAFSIR AL-AZHAR, AND TAFSIR MARĀH LABĪD - Fawaid, Ahmad; Zayyadi, Ach.; Amatillah, Alvina; Wirendri, Dwiki Oktafiana (MUSHAF: Jurnal Tafsir Berwawasan Keindonesiaan, 2021)
This article aims to figure out Indonesian commentators perspectives on the position of women in the domestic and public sphere. This research comes from the question; Has the patriarchal identity that existed in Indonesia influenced Indonesian commentators perspectives in interpreting the Koran?  And what is Indonesian commentators perspective on women’s leadership in the public sphere? With the literary method and critical analysis of their works, tafsīr al-Misbah, Tafsīr al-Azhar, and Tafsīr Marāh} Labīd, this research resulted in the following findings and conclusions. First, in essence, the three Indonesian commentators did not give permission to women to become leaders in the household, even they have different reasons. Nawāwī al-Bantānī considers men to be leaders for their wives, because men has the potential to educate them, has intellectual and physical strength. Hamka gave consideration to Indonesian traditions and culture. Meanwhile, Quraish Shihab argues that a man is the leader over his wife because of the psychological and character considerations of men who are more assertive. Second, regarding women’s leadership in the public sphere, Quraish Shihab and Hamka allow women to become leaders for men as long as they have sufficient criteria. Meanwhile al-Nawāwī did not provide a clear explanation of the status of women’s leadership in the public sphere. The findings in this study also confirm that, in addressing the problem of women, the Indonesian commentators has a paradigm shift from time to time, this is due to sociological factors and conditions surrounding the interpreter.